2014
DOI: 10.1097/ta.0b013e3182aafcd5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with trauma clinic follow-up compliance after discharge

Abstract: BACKGROUND:Disparities in access to postdischarge services for trauma patients exist, and clinic follow-up remains an important avenue to ensure initial and continued access to postdischarge services. In addition, follow-up is vital to rigorous long-term trauma outcomes research. However, there is a relative paucity of literature specifically addressing clinic follow-up. The purposes of this study were to elucidate factors associated with clinic follow-up compliance and noncompliance after discharge from an ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 12 publications
5
48
1
Order By: Relevance
“…Several factors were associated with functional outcomes following orthopedic surgeries, such as the characteristic of fractures, quality of reduction and fixation, complications, rehabilitation protocol, patients' compliance, and so on [23][24][25][26][27][28]. During the study period, the principles, implants, surgical techniques, and physical therapies for treating pelvic and acetabular fractures were similar in all patients.…”
Section: Discussionmentioning
confidence: 96%
“…Several factors were associated with functional outcomes following orthopedic surgeries, such as the characteristic of fractures, quality of reduction and fixation, complications, rehabilitation protocol, patients' compliance, and so on [23][24][25][26][27][28]. During the study period, the principles, implants, surgical techniques, and physical therapies for treating pelvic and acetabular fractures were similar in all patients.…”
Section: Discussionmentioning
confidence: 96%
“…1 However, previous studies of trauma patients have demonstrated poor rates of outpatient follow-up. 37,38 Stewart and Chen found that 66% of patients with isolated facial trauma attended their first follow-up appointment, but only 46% kept their recommended follow-up care. 39 Thus, given the low rate of follow-up, future multicenter studies on facial fractures that include follow-up data are needed to further evaluate whether our findings are representative of actual national rates of interventions in trauma subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Similar low rates of compliance with postoperative follow-up visits have been previously reported at the same medical center. 21 This was an unfunded study; therefore, patients were not compensated for returning to clinic. It is possible that patients returning after 2 weeks may have created a negative bias; patients who expected shorter time to return to normal function were more likely to return.…”
Section: Discussionmentioning
confidence: 99%